Peculiarities of Multilingual Films in the Context of Audio Visual Translation - Alosevičienė, Eglė (Respectus Philologicus, 2020)
The present article investigates the most topical issues of the genre and translation of the multilingual film (also referred to as „polyglot film“). The definition of this type of film is based on the use of several different languages and their ‘collision’ in a feature film. In this sense, the multilingual film is a formal genre similar to, e.g., the musical, where, instead of a combination of movement and singing, a combination of several languages prevails. It is also denoted by reiterating combinations of actions and character constellations, specific patterns (odyssey, integraa The present article investigates the most topical issues of the genre and translation of the multilingual film (also referred to as “polyglot film”). The definition of this type of film is based on the use of several different languages and their “collision” in a feature film. In this sense, the multilingual film is a formal genre similar to, e.g., the musical where instead of a combination of movement and singing a combination of several languages prevails. It is also denoted by reiterating combinations of actions and character constellations, specific patterns (odyssey, integration, translation), aptitude to puns, search for internationally clear vocabulary. On the other hand, a question may be raised whether the creator of a film deliberately selects the tradition of multilingualism, whether a multilingual film is consciously intended. In this case, the concept of the genre is heavily debatable. The multilingual film was developed in the 1930s, after the completion of the epoch of silent film. Since the 1990s, the multilingual film has been employed to draw attention to the issues of migration and diasporas. In the context of audio-visual translation, the multilingual film is prominently challenging. When dubbing, the film is adapted to the language and culture of translation while eliminating multilingualism. When subtitling, multilingualism is preserved by keeping the original soundtrack, and different languages may be highlighted by employing subtitles of different types (differentiating by font, colour, etc.). When employing voice-over, synchrony and isochrony of various types are essential. tion, translation), aptitude to puns, search for internationally clear vocabulary. On the other hand, a question may be raised whether the creator of a film deliberately selects the tradition of multilingualism, whether a multilingual film is consciously intended. In this case, the concept of the genre is heavily debatable. Multilingual film was developed in the 1930s, after the completion of the epoch of silent film. Since the 1990s, multilingual film has been employed to draw attention to the issues of migration and diasporas. In the context of audio visual translation, multilingual film is prominently challenging. When dubbing, the film is adapted to the language and culture of translation while eliminating multilingualism. When subtitling, multilingualism is preserved by keeping the original soundtrack, and different languages may be highlighted by employing subtitles of different types (differentiating by font, colour, etc.). When employing voice-over, synchrony and isochrony of various types are essential.